2016
DOI: 10.4194/1303-2712-v16_4_02
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Whether the inclusion of the various sources of commercially available dietary additives [ginger (GG), cheonggukjang (CJ), blueberry (BB), persimmon (PM), tomato (TT), broccoli (BC) and yacon (YC)] has an effect on growth, body composition, and challenge test survival of juvenile rockfish Sebastes schlegeli was investigated. Twenty-four groups of 70 fish (1680 in total) were each fed one of eight experimental diets: a control diet (Con) without additives, and diets containing GG, CJ, BB, PM, TT, BC or YC. Fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Moreover, ginger powder administration significantly improved O. niloticus resistance against S. agalactiae infection [ 17 ]. Dietary ginger powder also positively impacted the treatment of Gram-positive and/or Gram-negative bacterial infections in S. schlegelii [ 33 , 34 , 57 ]. Lee et al [ 34 ] reported that 1% GRJE-supplemented S. schlegelii groups attained a higher probability of survival against Gram-negative bacteria ( V. harveyi ) compared with groups that did not receive GRJE supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ginger powder administration significantly improved O. niloticus resistance against S. agalactiae infection [ 17 ]. Dietary ginger powder also positively impacted the treatment of Gram-positive and/or Gram-negative bacterial infections in S. schlegelii [ 33 , 34 , 57 ]. Lee et al [ 34 ] reported that 1% GRJE-supplemented S. schlegelii groups attained a higher probability of survival against Gram-negative bacteria ( V. harveyi ) compared with groups that did not receive GRJE supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies (Kim et al, 2016;Kim et al, 2018;Lee et al, 2020; revealed that dietary inclusion of YC enhanced the growth performance and improved their antibacterial activities against E. tarda, Streptococcus iniae, S. parauberis, and Vibrio anguillarum in rockfish (Sebastes schlegeli).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have demonstrated that GG has antimicrobial, anti-inflammatory, and anti-oxidative properties (Akbarian et al, 2011;Akintobi et al, 2013;Chrubasik et al, 2005;Grzanna et al, 2005;Kim et al, 2007;Masuda et al, 2004;Minghetti et al, 2007) as well as the ability to influence immune function in fish (Ali et al, 2008;Tan & Vanitha, 2004). In rockfish, GG supplemented diets achieved improvement in weight gain, feed utilization, and survival rate in comparison to a diet without any additive against S. parauberis, S. iniae, and E. tarda (Kim et al, 2016;Kim et al, 2018;. In addition, dietary supplementation of GG has been reported to ameliorate the non-specific immune responses and disease resistance to various pathogens in tilapia (Oreochromis mossambicus) and Asian seabass (Lates calcarifer) (Immanuel et al, 2009;.…”
Section: Introductionmentioning
confidence: 99%
“…22.0%) (KOSIS, 2016). (Kim et al, 2001;Cho et al, 2015), (Lee and Kim, 2009), (Lee, 2002), (Lee et al, 2000;Mizanur et al, 2014), (Lee et al, 1996;Jeon et al, 2014) lysozyme (Hwang et al, 2013) Vibrio alginolyticus (Kim et al, 1999) .…”
mentioning
confidence: 99%
“…Staphylococcus aureus . Kim et al (2016) YC . [Ginger (GG), Zingiber officinale Roscoe] gingerols shogaol (Sebiomo et al, 2011), (Ekwenye and Elegalam, 2005) (Balestra et al, 2011) .…”
mentioning
confidence: 99%